2014
DOI: 10.1007/s11356-014-3452-0
|View full text |Cite
|
Sign up to set email alerts
|

Sources and elemental composition of summer aerosols in the Larsemann Hills (Antarctica)

Abstract: Atmospheric aerosols play a major role in the global climate change. A better physical characterization of the chemical composition of atmospheric aerosols, especially in remote atmosphere, is an important step to reduce the current uncertainty in their effect on the radiative forcing of the climate. In the present work, surface aerosols have been studied over the Southern Ocean and over Bharati, Indian Research Station at Larsemann Hills at the Antarctic coast during the summer season of 2009-2010. Aerosol sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 51 publications
2
18
0
Order By: Relevance
“…Thus most of the particle mass were in the coarse mode, and the increasing primary emissions with wind were the main cause for the deviation of average and median mass concentration values. Also previous studies have reported relatively similar mass concentrations on the order of some μg m −3 measured at the Antarctic coastal sites (Artaxo and Rabello, 1992;Mazzera et al, 2001;Chaubey et al, 2011;Budhavant et al, 2015), yet not such a significant increase towards the coarse mode was observed before. All studies, however, are consistent with mass concentration seasonal cycle showing higher values in winter.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Thus most of the particle mass were in the coarse mode, and the increasing primary emissions with wind were the main cause for the deviation of average and median mass concentration values. Also previous studies have reported relatively similar mass concentrations on the order of some μg m −3 measured at the Antarctic coastal sites (Artaxo and Rabello, 1992;Mazzera et al, 2001;Chaubey et al, 2011;Budhavant et al, 2015), yet not such a significant increase towards the coarse mode was observed before. All studies, however, are consistent with mass concentration seasonal cycle showing higher values in winter.…”
Section: Discussionmentioning
confidence: 56%
“…Also it should be noted that calcium is not the best marker for mineral dust due to its presence in the seawater. It has also been found to be significantly enriched in Antarctic coasts and seawater, which suggests additional anthropogenic sources of Ca 2+ are present (Préndez et al, 2009;Budhavant et al, 2015). Calcium enrichment has also been observed in the Arctic as suggested by very recent evidence by Salter et al (2016).…”
Section: Chemical Compositionmentioning
confidence: 83%
See 1 more Smart Citation
“…S6) during the austral summer period, the growth of DMS(P)rich Phaeocystis may therefore be more favorable in the Bellingshausen Sea. Sea-surface warming and freshening is commonly associated with a shallowing of the mixed layer depth (Capotondi et al, 2012). The warming trend has shown the spatial complexity across the Antarctic Ocean in recent decades (Turner et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the measurements over Maitri, Gadhavi and Jayaraman (2004) reported that the total aerosol mass concentration at surface level is of 7 µg m -3 for the PM10 particles with significant (day-to-day) variations. Based on the measurement during the 2009-2010, Budhavant et al (2015 reported that the mean mass concentration for PM10 aerosols over southern ocean was found to be 13.4 µg m -3 and over coastal Antarctica near Bharati was found to be 5.13 µg m -3 . They further reported that the elements of anthropogenic origin (Eg.…”
Section: Indian Efforts On Aerosol Studies Over Antarcticamentioning
confidence: 99%